Ephesians - Roberts, Mark D. (Grand Rapids, Michigan : Zondervan, 2016)
A new commentary for today's world, The Story of God Bible Commentary explains and illuminates each passage of Scripture in light of the Bible's grand story. The first commentary series to do so, SGBC offers a clear and compelling exposition of biblical texts, guiding everyday readers in how to creatively and faithfully live out the Bible in their own contexts. This commentary includes three easy-to-use sections designed to help readers live out God's story : 1. Listen to the Story : Includes complete NIV text with references to other texts at work in each passage, encouraging the reader to hear it within the Bible's grand story ; 2. Explain the Story : Explores and illuminates each text as embedded in its canonical and historical setting ; 3. Live the Story : Reflects on how each text can be lived today and includes contemporary stories and illustrations to aid preachers, teachers, and students.--Publisher's description.
Ephesians 1:1-2 -- Ephesians 1:3-14 -- Ephesians 1:15-23 -- Ephesians 2:1-10 -- Ephesians 2:11-22 -- Ephesians 3:1-13 -- Ephesians 3:14-21 -- Ephesians 4:1-6 -- Ephesians 4:7-16 -- Ephesians 4:17-5:2 -- Ephesians 5:3-14 -- Ephesians 5:15-20 -- Ephesians 5:21-33 -- Ephesians 6:1-4 -- Ephesians 6:5-9 -- Ephesians 6:10-20 -- Ephesians 6:21-24.
Includes bibliographical references and indexes.
Keywords: Bible. -- Commentaries